Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

Thermal response of heterolithic deposits in flooded coal mines: implication for heat storage potential - Mylene Receveur; Andres Gonzalez Quiros; Alison Monaghan; Vanessa Starcher; Kyle Walker-Verkuil; David Boon; Jeroen van-Hunen (Geothermics, 2026)

Vulnerability and psychosocial impacts of extreme weather events among young people in Australia - Myriam Ziou; Daniel Z.Q. Gan; Bronwyn Boon; Shu Mei Teo; Jana M. Menssink; Wenhua Yu; Catherine L. Smith; Rebecca Patrick; Hasini Gunasiri; Nicholas J. Fava; David G. Baker; Vivienne Browne; et al. (Environmental Research, 2025)

Co-design in policy development: Leveraging opportunities, addressing challenges, and proposing solutions for inclusive governance - Lessons from England - Judith Tsouvalis; Ruth Little; José Fajardo-Escoffie; Susan E. Hartley; David Christian Rose; Bianca Ambrose-Oji; Auvikki de Boon; Siobhan Maderson; Julie Urquhart (Land Use Policy, 2025)

To adapt or not to adapt, that is the question. Examining farmers’ perceived adaptive capacity and willingness to adapt to sustainability transitions - Auvikki de Boon; Camilla Sandström; David Christian Rose (Journal of Rural Studies, 2024)

An elephant in the glasshouse? Trade-offs between acceleration and transformation in COVID-19 vaccine innovation policies - Linda van de Burgwal; Tom van der Valk; Hannes Kempter; Manuel Gadau; David Stubbs; Wouter Boon (Environmental Innovation and Societal Transitions, 2023)

A psychometric approach to assess justice perceptions in support of the governance of agricultural sustainability transitions - Auvikki de Boon; Sabrina Dressel; Camilla Sandström; David Christian Rose (Environmental Innovation and Societal Transitions, 2023)

First comparison of sampler surface areas for atmospheric microfibre deposition - Alexander Matthew David Finnegan; Rebekah Süsserott; Lip-Hwee Koh; Wei-Boon Teo; Sarah E. Gabbott; Chris Gouramanis (Environmental Monitoring and Assessment, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cycle Length Evaluation in Persistent Atrial Fibrillation Using Kernel Density Estimation to Identify Transient and Stable Rapid Atrial Activity - Szabolcs Z. Nagy; Patrick Kasi; Valtino X. Afonso; Nathaniel Bird; Brian Pederson; Ian E. Mann; Steven Kim; Nicholas W. F. Linton; David C. Lefroy; Zachary I. Whinnett; Fu Siong Ng; Michael Koa-Wing; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose Left atrial (LA) rapid AF activity has been shown to co-localise with areas of successful atrial fibrillation termination by catheter ablation. We describe a technique that identifies rapid and regular activity. Methods Eight-second AF electrograms were recorded from LA regions during ablation for psAF. Local activation was annotated manually on bipolar signals and where these were of poor quality, we inspected unipolar signals. Dominant cycle length (DCL) was calculated from annotation pairs representing a single activation interval, using a probability density function (PDF) with kernel density estimation. Cumulative annotation duration compared to total segment length defined electrogram quality. DCL results were compared to dominant frequency (DF) and averaging. Results In total 507 8 s AF segments were analysed from 7 patients. Spearman’s correlation coefficient was 0.758 between independent annotators ( P < 0.001), 0.837–0.94 between 8 s and ≥ 4 s segments ( P < 0.001), 0.541 between DCL and DF ( P < 0.001), and 0.79 between DCL and averaging ( P < 0.001). Poorer segment organization gave greater errors between DCL and DF. Conclusion DCL identifies rapid atrial activity that may represent psAF drivers. This study uses DCL as a tool to evaluate the dynamic, patient specific properties of psAF by identifying rapid and regular activity. If automated, this technique could rapidly identify areas for ablation in psAF.

Correction to: A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)

A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)
There is great need for coordination around standards and best practices in neuroscience to support efforts to make neuroscience a data-centric discipline. Major brain initiatives launched around the world are poised to generate huge stores of neuroscience data. At the same time, neuroscience, like many domains in biomedicine, is confronting the issues of transparency, rigor, and reproducibility. Widely used, validated standards and best practices are key to addressing the challenges in both big and small data science, as they are essential for integrating diverse data and for developing a robust, effective, and sustainable infrastructure to support open and reproducible neuroscience. However, developing community standards and gaining their adoption is difficult. The current landscape is characterized both by a lack of robust, validated standards and a plethora of overlapping, underdeveloped, untested and underutilized standards and best practices. The International Neuroinformatics Coordinating Facility (INCF), an independent organization dedicated to promoting data sharing through the coordination of infrastructure and standards, has recently implemented a formal procedure for evaluating and endorsing community standards and best practices in support of the FAIR principles. By formally serving as a standards organization dedicated to open and FAIR neuroscience, INCF helps evaluate, promulgate, and coordinate standards and best practices across neuroscience. Here, we provide an overview of the process and discuss how neuroscience can benefit from having a dedicated standards body.

Mainstreaming climate change adaptation into pro-poor development initiatives: evidence from local economic development programmes in Ghana - Albert Ahenkan; David Nawiene Chutab; Emmanuel Kwesi Boon (Climate and Development, 2021)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Treading Water: Tools to Help US Coastal Communities Plan for Sea Level Rise Impacts - Emily A. Smith; William Sweet; Molly Mitchell; Ricardo Domingues; Christopher P. Weaver; Molly Baringer; Gustavo Goni; John Haines; J. Derek Loftis; John Boon; David Malmquist (Frontiers in Marine Science, 2019)

Customized media based on miniaturized screening improve growth rate and cell yield of methane-oxidizing bacteria of the genus Methylomonas - Sven Hoefman; David van der Ha; Nico Boon; Peter Vandamme; Paul De Vos; Kim Heylen (Antonie van Leeuwenhoek, 2014)

Carbon and nitrogen mass balance during flue gas treatment with Dunaliella salina cultures - Till Harter; Peter Bossier; Johan Verreth; Samuel Bodé; David Van der Ha; Ann-Eline Debeer; Nico Boon; Pascal Boeckx; Wim Vyverman; Nancy Nevejan (Journal of Applied Phycology, 2013)

Selection of associated heterotrophs by methane-oxidizing bacteria at different copper concentrations - David van der Ha; Inka Vanwonterghem; Sven Hoefman; Paul De Vos; Nico Boon (Antonie van Leeuwenhoek, 2013)

Two-dimensional variational analysis of near-surface moisture from simulated radar refractivity-related phase change observations - Ken-ichi Shimose; Ming Xue; Robert D. Palmer; Jidong Gao; Boon Leng Cheong; David J. Bodine (Advances in Atmospheric Sciences, 2013)

Observations and implications of damage from the magnitude Mw 6.3 Christchurch, New Zealand earthquake of 22 February 2011 - Sean Wilkinson; Damian Grant; Elizabeth Williams; Sara Paganoni; Stuart Fraser; David Boon; Anna Mason; Matthew Free (Bulletin of Earthquake Engineering, 2013)

Bronfenbrenner’s bioecological theory for modelling community resilience to natural disasters - Helen J. Boon; Alison Cottrell; David King; Robert B. Stevenson; Joanne Millar (Natural Hazards, 2012)